Elevation, aspect, and habitat heterogeneity determine plant diversity and compositional patterns in the Kashmir Himalaya - Wani, Zishan A.; Negi, Vikram S.; Bhat, Jahangeer A.; Satish, K. V.; Kumar, Ashish; Khan, Sajid; Dhyani, Rupesh; Siddiqui, Sazada; Al-Qthanin, Rahmah N.; Pant, Shreekar (Frontiers in Forests and Global Change, 2023)
Elevational gradient, slope and aspect offer a unique opportunity to explore the response of plant species under changing environmental conditions. The present study aims to analyze the species diversity and distribution patterns with respect to altitude, aspect as well as habitat types in the Kashmir Himalaya. Considering major aspects and habitats, a total of 123 representative sites were selected along the elevational gradients for the present study. The plant species composition of each selected site was studied by organized sampling following standard ecological methods. During the present study, a total of 361 vascular plant species belonging to 71 families and 214 genera were identified from the study area. At the lower altitudes, the southern aspect and drier habitats showed highest diversity. Also, a significant amount of compositional dissimilarity was observed in between the studied aspects, habitats and elevation belts and was mainly due to species turnover rather than the nestedness component. Further, among the studied variables, altitude turned out to be the most important contributing variable explaining greatest amount of variation in the species composition. The paired effect of altitude and habitat explained the maximum variation in plant species composition. It may be concluded that the floristic diversity should be studied not only with reference to elevational gradients but should include aspects and habitats as well. The current study will act as a template in this direction and similar study must be replicated in other parts of Himalayan region in future, so as to increase our understanding about the distribution and preferences of plant species in mountainous zones. This in turn will be immensely helpful in the conservation and sustainable utilization of resources in these eco-fragile regions.